Refractive Errors and Risk Factors for Myopia in Primary School Students in Urumqi - Meng Liu; Han Qin; Yan Wang; Yunxian Gao (Applied Bionics and Biomechanics)
Objective. To investigate the prevalence of refractive errors and risk factors for myopia in primary school students in Saybag District of Urumqi. Methods. A total of 972 primary school students in two elementary schools in Saybag District were included in this study which was conducted from June 2019 to November 2019. Uncorrected visual acuity test and noncycloplegic autorefraction were performed, and their visual acuity was analyzed. Multivariate regression analysis was performed to predict risk factors for myopia. Results. Myopia was the most frequent refractive error among primary school students aged 7-11 in Sayibake District, Urumqi City, with a prevalence rate of 60.39%, and mainly mild myopia. The proportion of myopia increased with age, and the proportion of females suffering from myopia was higher than that of males, and the proportion of students from the Han ethnic group suffering from myopia was also higher than that of the other ethnic groups. The students mainly suffered from mild myopia, and the degree of myopia was related to age and gender, regardless of ethnicity. In addition, multivariate regression analysis showed that age and gender were the influencing factors of myopia occurrence and progression Conclusion.Our study results showed a significant prevalence of myopia in pupils aged 7-11 years in Saybag District of Urumqi is affected by gender and age and not by ethnicity.